Flight model measurements of the porous plug and film flow suppression system for the ASTRO-H Soft X-ray Spectrometer dewar. (March 2016) - Ezoe, Yuichiro; Ishikawa, Kumi; Mitsuishi, Ikuyuki; Ohashi, Takaya; Mitsuda, Kazuhisa; Fujimoto, Ryuichi; Murakami, Masahide; Kanao, Kenichi; Yoshida, Seiji; Tsunematsu, Shoji; DiPirro, Michael; Shirron, Peter; et al.
Highlights: We designed and fabricated a flight model of a porous plug and film flow suppression system for ASTRO-H SXS. We measured the mass flow rate and film flow of the system at component level and in the flight model dewar. Phase separation and film flow suppression of super fluid helium are confirmed. Abstract: Flight model measurements of a porous plug phase separator and a film flow suppression system for the ASTRO-H Soft X-ray Spectrometer dewar are described. ASTRO-H is the sixth Japanese astronomy satellite and will be launched in 2016. It carries the Soft X-ray Spectrometer consisting of an X-ray optic and an X-ray microcalorimeter system operated at 50 mK. Superfluid liquid He is employed as a part of the cooling system. A wide range of He flows from 28 μ g/s to 3.2 mg/s in various operation cases must be safely vented under zero gravity. At the same time, superfluid He film flow through the vent line must be suppressed to <2 μ g/s in a nominal case to avoid extra loss of the liquid He. For this purpose, a porous plug phase separator together with a film flow suppression system is installed. To verify its performance, the mass flow rates and the film flow rate of the flight model system were measured at component level. The mass flow rates at various He tank temperatures (1.15, 1.30, 1.50, and 2.00 K) were obtained and also the film flow rate was measured at 1.15 K. Then, the mass flow rates were measured after installing the whole system into a flight model dewar at the He tank temperature of 1.16, 1.30, 1.50, and 2.00 K. The dewar was tilted so that the porous plug located at the top of the dewar is immersed in the liquid He and the porous plug separates the liquid and vapor He by the thermomechanical effect as in orbit. The obtained mass flow rates and the film flow rate in these tests were confirmed to meet the requirements and to be consistent with each other. No abnormal event such as large mass flow rates was observed. All these experimental results strongly suggest that this flight model of the porous plug and the film flow suppression system will work properly in space.